(untitled) (Medical Forum Monthly, 2023)
Objective: To compare the efficacy of ondansetron and metoclopramide in children with gastroenteritis with vomiting. Study Design: cross-sectional study Place and Duration of Study: This study was conducted at the Pediatric Unit, Lady Reading Hospital Peshawar from May, 2019 to November, 2019. Materials and Methods: A total of 112 cases were enrolled and two groups made. Children in group A were treated with rehydration therapy and metoclopramide for vomiting whereas children in group B were treated with rehydration therapy plus ondansetron. Patients were monitored for vomiting at one and 06 hours of administration of antiemetic drugs. Results: Of the total 112 cases, 66 (58.9 %) were male, 46 (41.1 %) were female patients. Mean age was 3.45 ± 1.70 years. Mean BMI was 22.32 ± 1.13 kg/m2 while 15 (13.4 %) of cases were obese. History of breastfeeding was noted in 73 (65.2%). Mean duration of illness was 4.24 ± 2.15 days, 106(64.6%) had a total duration of 7 days. Of total cases 81 (72.3 %) were vaccinated, 31 (27.7 %) unvaccinated. Out of 112 cases, 100 responded well to treatment, in Group A the efficacy was 46 (82.1%) whereas in group B it was 54 (96.4%) Conclusion: Ondansetron was found to be safe, efficacious, for treating children with acute gastroenteritis with vomiting. And having a higher efficacy than metoclopramide, hence it is concluded that ondansetron can be safely given to children with acute gastroenteritis with vomiting